2014
DOI: 10.1063/1.4899003
|View full text |Cite
|
Sign up to set email alerts
|

The influence of porosity on the elasticity and strength of alumina and zirconia ceramics

Abstract: Abstract. This work investigates the behavior of porous alumina (with the porosity ranging from 18% to 70%) and zirconia (with the porosity ranging from 10% to 60%) ceramics when subjected to deformation by compression and shearing. The analysis of stress-strain curves showed that there is a transition from a typical brittle state for relatively dense ceramics, to a pseudo-plastic one for ceramics with high porosity. The values of the effective Young's modulus, effective shear modulus and Poisson's ratio decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 4 publications
2
8
0
Order By: Relevance
“…This difference can be attributed to the layer-line and layer-plane orientations, which were perpendicular to the plane of the maximum normal stress [33]. It has also been reported that the elastic modulus and Poisson's ratio of zirconia ceramics decrease with increasing pore-space volume [43]. Thus, the factors that affect the mechanical properties of SLA-manufactured zirconia specimens are not only affected by the building direction, but also by the apparatus and manufacturing process (from additive manufacturing to sintering).…”
Section: Discussionmentioning
confidence: 98%
“…This difference can be attributed to the layer-line and layer-plane orientations, which were perpendicular to the plane of the maximum normal stress [33]. It has also been reported that the elastic modulus and Poisson's ratio of zirconia ceramics decrease with increasing pore-space volume [43]. Thus, the factors that affect the mechanical properties of SLA-manufactured zirconia specimens are not only affected by the building direction, but also by the apparatus and manufacturing process (from additive manufacturing to sintering).…”
Section: Discussionmentioning
confidence: 98%
“…Pore structure was reported to be correlated with mechanical properties, such as stiffness and compress yield stress, in an engineered porous material . The effective Young’s modulus reduced with increasing porosity in ceramics . However, the characterization of both biofilm stiffness and pore structure has not been conducted.…”
Section: Discussionmentioning
confidence: 99%
“…35 The effective Young's modulus reduced with increasing porosity in ceramics. 53 However, the characterization of both biofilm stiffness and pore structure has not been conducted. Our results revealed that the abundant long or large water-filled connecting throats can contribute to the reduction of force measured during indentation into silicate biofilms under water.…”
Section: ■ Discussionmentioning
confidence: 99%
“…The mineralogical composition of these powder mixtures is described in the Table 2 and the typical microstructure and chemical components are shown in Figure 1. On the basis of the earlier experiments with alumina [34][35][36][37] and zirconia [38][39][40] of the authors in this research to the conventional floor tiles powder Martoxid KMS-94 alumina ( Figure 2) and TZP zircon-dioxide ( Figure 3) powders were added in different ratios.…”
Section: Materials and Experimentsmentioning
confidence: 99%